Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kepatuhan Wajib Pajak Dalam Pelaporan Pajak - Saydidah, Qaulan; Seventeen, Winny Lian (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the factors that influence the level of corporate taxpayer compliance in tax reporting. The method used is a literature study. The results of the study obtained that corporate taxpayer compliance is influenced by several main factors, namely the complexity of tax regulations, audit and sanction risks, and ethics and compliance culture within the company. Audit and sanction risks are also important drivers of tax compliance, where companies that feel the threat of audits and severe sanctions tend to be more compliant. Ethical culture within the company plays a significant role in encouraging compliance, where companies that have strong ethical values ??and social responsibility are more likely to comply with tax obligations. In conclusion, increasing tax compliance can be achieved through regulatory simplification, effective law enforcement, and developing a culture of compliance within the company